MOTIVATIONAL AND ADMINISTRATIVE SPHERE OF BUSINESS WOMEN'S ACTIVITIES - Sanakulovna, Shoyimova Shoxista; Asrarovna Mirzaeva, Mirzaeva Nargiza; Kizi, Shaxlo Ruzmat (International Journal of Psychosocial Rehabilitation, 2020)
– This article is a theoretical and empirical study of the motivational and volitional spheres of women's entrepreneurship, which recognizes that the effectiveness and development of entrepreneurial activity depends on the motivation to succeed, willpower, risk, self-confidence, communication and organizational skills.